Regular observations of the geomagnetic field at the Ógyalla observatory (present-day Hurbanovo) near the turn of the 20th century, including magnetic storms accompanied by auroras in March 1894, September 1898, and October 1903 - VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; VÝBERČI, Dalibor; KOČI, Eduard (Contributions to Geophysics and Geodesy, 2024)
From 1893 to 1905, the values of the geomagnetic field recorded three times a day are available from the Ógyalla magnetic observatory. We introduce these unique records, and at the same time, we provide an analysis of three noteworthy magnetic storms from this period, namely the events on 30 March 1894, 9 September 1898, and 31 October 1903. In addition to violent magnetic variations, remarkable auroras were observed in Central Europe during these events. The analysed events indicate that the source of the most intense, potentially dangerous geomagnetic disturbances can be the electric currents of the auroral oval or the field-aligned currents connected to the auroral oval.